#### Answer

$-64$

#### Work Step by Step

$\bf{\text{Solution Outline:}}$
To simplify the given expression, $
(-32i)(-2i)
,$ multiply the numerical coefficients and multiply the $i$'s as if it were a literal coefficient. Then use $i^2=-1$.
$\bf{\text{Solution Details:}}$
Multiplying the numerical coefficients and the $i$'s result to
\begin{array}{l}\require{cancel}
(-32\cdot-2)(i\cdot i)
\\\\=
64i^2
.\end{array}
Since $i^2=-1,$ the expression above is equivalent to
\begin{array}{l}\require{cancel}
64(-1)
\\\\=
-64
.\end{array}